MORPHOLOGICAL IDENTIFICATION OF SEA CUCUMBER AND PROXIMATE ANALYSIS OF THE HABITAT SUBSTRATE OF MUDY SEA CUCUMBER ON MOLOSING ISLAND AND BIAU BEACH BOLAANG MONGONDOW REGENCY - Jennifer Pangulimang; Revolson A Mege; Nonny Manampiring; Nova L.I.M Ogi (Universitas Negeri Manado, 2023)
Sea Cucumbers belong to the phylum Echinodermata, class Holothuroidea. These creatures are commonly found in areas near coral reefs, sandy waters, seaweed, seagrass beds, and muddy sands. This research aims to identify the various species of Sea Cucumbers in the waters around Molosing Island and Biau Beach, Bolaang Mongondow Regency. Furthermore, the research seeks to determine the nutritional content of the muddy substrate where Sea Cucumbers reside. The study involves observing the form, colour, and patterns (morphology) of Sea Cucumbers and testing the nutritional content of their muddy habitat substrate using proximate analysis with the SNI by difference method. The identification results of the form, colour, and patterns of Sea Cucumbers at Molosing Island and Biau Beach, Bolaang Mongondow Regency, reveal three species of Sea Cucumbers from different genera: Holothuturia and Stichopus. One species on Molosing Island is Holothuria leucospilota, while two on Biau Beach are Stichopus horrens and Stichopus vastus. Proximate analysis of the muddy habitat substrate of Sea Cucumbers includes the following parameters: ash content, protein content, crude fiber content, and fat content.